Keberterimaan terhadap Sistem Layanan Pendidikan Inklusif sebagai Salah Satu Pilar Pembaharuan Pendidikan - Hermanto Hermanto (Fakultas Ilmu Pendidikan UNY, 2011)
The existence of individuals with special needs have long been aware of. Similarly, educational servicesfor individuals with special needs also have long existence. Speaking of education for individuals with special needs, so was slow in Indonesia, especially when we speak of equality of educationfor them. Educational equality in question is an inclusive education for individuals with special needs within the school system to